oreign experience of compensation of damage caused by a subject of public administration to a private person and the possibility of its use in Ukraine - Yakovych Nastyuk, Vasyl; Tkachenko, Vita; Koval, Alla; Martseliak, Svitlana (DIXI, 2021)
This article carries out an analysis and a comparison of successful experience of foreign countries on compensation of the damage caused by the subject of public administration to the private person, and possibilities of its use in Ukraine are defined. It is pointed out that in order to achieve the effective functioning of the public administration system, which would respect all fundamental rights, freedoms and legitimate interests of individuals, Ukraine needs to pay attention to the state of affairs in this area in Western Europe and North America. Emphasis is placed on the fact that only a state that properly complies with the legislation related to the protection of individuals, in the performance of public administration tasks and responsibilities of public administration, can create and maintain a high level of economic development and social welfare. In particular, this applies to the legal norms of national and international law, which in one way or another regulate the procedures for compensation (or compensation) to individuals by the state (its representative bodies), in the case when the first damage or damage from the state is related to public administration. The author’s definitions of the terms “public administration”, “compensation” and “methods of compensation” are offered. In addition, the systems of functioning of such a state and public institution as a mechanism of state compensation for damage caused to individuals are studied and compared, and the impact of the quality of functioning of such a mechanism on the overall efficiency of the state system is analyzed.